Model Transformasi Digital pada Komunikasi Pemasaran Pertanian di Indonesia - Noviarta Rizky Manik (Jurnal Syntax Admiration, 2024)
Marketing communication can also be interpreted as a two-way exchange of information between parties or institutions that are visible in marketing. The use of digital media as a means of communication is currently used to produce, reproduce, distribute or disseminate and convey information in marketing activities. Marketing digitalization will certainly make marketing activities simpler, faster, more accurate, easier, cheaper, more effective and efficient through marketing digitalization. TaniHub as e-commerce in the agricultural sector applies a digital communication model to marketing in the agricultural sector, namely (1) advertising, (2) sales promotion, (3) events and experiences, (4) public relations and publicity, (5) direct marketing, (6) interactive marketing, (7) word of mouth marketing and (8) personal selling. The aim of this research is to determine the communication transformation model applied by TaniHub in running its business. By using qualitative research and interview methods with TaniHub, the results of this research show that the application of a communication model using eight communication models from Kotler can improve marketing and increase TaniHub e-commerce customers, both from farmer partners and agricultural product buyers.